Peran Waralaba Terhadap Bisnis Alternatif UMKM Es Teh Jumbo - Emalia Yunika; Rusnandari Retno Cahyani (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
With the current situation and conditions where employment is very difficult, it is suitable for many people to become entrepreneurs in the business world. The purpose of this research in order to formulate the question is to find out the analysis of franchising other tea companies. In this article, the researcher uses the literature study method by collecting literature (material materials) sourced from books, journals, and other sources related to the science of franchising and umkm iced tea.jumbo tea application system is any level of ordinary business management called a company / institution When you enter this business, one must go through a long process that must be followed and implemented or Details (SOP / Standard Operating Procedure). The franchise agreement has specific provisions that must be contained and regulated in the franchise agreement. One of the important clauses in the franchise agreement concerns confidentiality.